Faktor Yang Mempengaruhi Advertising Value Dan Pengaruhnya Terhadap Attitude Toward Ads Dan Brand Awareness Pada Konsumen Brand Avoskin - Dinda Ayu Sieradianto Angelia; Tarysha Aulya Putri Rany; Henny Firizqi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study explores the factors that affect advertising value and their role in shaping the attitude toward advertisement and brand awareness among consumers of Avoskin. The variables examined are irritation and entertainment, which impact the value of advertising. This study employs a quantitative approach, utilizing a survey method with 100 participants who are consumers of Avoskin products. Data was collected through an online questionnaire and analyzed using the Partial Least Squares (PLS) method. The study findings indicate entertainment positively impacts advertising value, whereas irritation does not have a significant impact. Furthermore, research has demonstrated that advertising value has a beneficial impact on attitude toward ads and brand awareness. These findings suggest important implications for Avoskin Brand to continue to improve the entertainment element in its digital advertising and minimize irritation in order to strengthen brand awareness and positive consumer attitudes towards advertising. This study also suggests that companies pay attention to the frequency and type of advertising displayed to maintain the effectiveness of marketing campaigns in an increasingly competitive market